STUDI KOMPARATIF HAK ASUH ANAK PASCA PERCERAIAN DALAM PERSPEKTIF HUKUM ISLAM DAN HUKUM PERDATA - NIM. A1011211074, EKA FATMAWATI (Fakultas Hukum Universitas Tanjungpura, 2025)
ABSTRACT One of the consequences of the dissolution of marriage is child custody, which is referred to in Islamic law as hadhanah and in civil law as guardianship or custodial rights. This study discusses the concept of child custody after divorce according to Islamic law and civil law, examined from the perspective of the principle of justice. The aim of this research is to analyze the similarities and differences in the concept of child custody after divorce in Islamic and civil law, based on the principle of justice. The method used in this research is qualitative research with a normative approach. Data collection was carried out using a descriptive-comparative method through statutory, conceptual, and comparative approaches. The data collection technique employed was library research, which involved studying primary sources and relevant secondary literature. The research findings show that the principle of justice in the concept of child custody according to Islamic law and civil law has both similarities and differences. Both legal systems are guided by the principle of the best interest of the child in determining custody, considering the opinion of a discerning (mumayyiz) child as a factor in the judge's decision. Custody rulings are not absolute and must still prioritize the child